Investigating Pedagogical Content Knowledge and Decision-Making on Algebraic Tasks - Mastuti, Ajeng Gelora (JRPM (Jurnal Review Pembelajaran Matematika), 2023)
Pedagogical Content Knowledge (PCK) tasks and decision-making are closely related to teaching and learning mathematics. This study aims to investigate teacher PCK in decision-making on different algebra tasks and to see activity in teacher-student interactions. This research is qualitative, with a research approach used as a case study. The participants in this study were only one teacher with different characteristics in mathematics tasks. Data collection consisted of primary research data from class observations, teacher interview transcripts, and researcher notes, while documents such as teacher notes were secondary data. Data analysis was carried out directly based on class observations and interviews. The findings in this study reveal teacher PCK through teacher decision-making regarding algebraic tasks in Swartz & Perkins (2016) three theories of thinking: generating ideas, clarifying ideas, and assessing the reasonableness of ideas.